CellCo: using metaphors to understand organizational identity - Jacobs, Claus D. (Henry Stewart Talks, 2018)
This case study examines an ‘embodied metaphor’ approach employed by a cellphone company we’re calling CellCo to explore the company’s organisational identity. The metaphorical representation of the company provided an important diagnostic element that guided the company on subsequent strategy formation.